A Bequest of Wings: Dialogical Teaching - Literature as a Mediational Tool - Falconer, Marc Stuart (My University, 2007)
This research report explores the unique nature of literature and its efficacy as a dialogically mediating tool. In this study, drawing primarily on the theories of Vygotsky and Bakhtin, the dialogical small-group teaching of nine A Level students is considered, (with the teaching aimed to be within this group’s Zone of Proximal Development) it was found axiomatic that there was a supporting framework of schemes, tropes, narrative role taking, schemata theory and genre, among other concepts. Qualitative analysis of the edited transcripts from eight consecutive seminars substantiates these theoretical presumptions and leads to the conclusion that literature, in this case the prescribed poems of Elizabeth Jennings, is an highly efficacious, dialogically mediating, pedagogical tool.
Student Number : 0111318E - M Ed research report - School of Education - Faculty of Humanities
Keywords: Bakhtin; Dialogical Teaching; Literature; Mediation; Schemata Theory; Vygotsky; Zone of Proximal Development